(untitled) (The Review of Diabetic Studies, 2025)
Yoga is an ancient discipline with profound therapeutic potential, as documented in classical Hatha Yogic texts. Among them, the Gheranda Samhita presents Saptanga Yoga, a structured sevenfold system integrating cleansing techniques, postures, breath control and meditative practices. This study systematically explores the therapeutic applications of Saptanga Yoga, evaluating its impact on cardiovascular health, respiratory efficiency, neural plasticity and stress regulation. A comprehensive integrative review of classical texts and modern empirical studies was conducted, critically analyzing its role in preventive healthcare, chronic disease management and mental well-being. Findings suggest that Saptanga Yoga fosters autonomic regulation, metabolic balance and psychological resilience, making it a promising complementary approach in integrative medicine. However, the study highlights lack of controlled clinical trials, emphasizing the need for empirical validation through randomized studies and neurophysiological assessments. By bridging ancient wisdom with modern evidence-based research, this paper advocates for incorporating Saptanga Yoga into contemporary therapeutic frameworks.